Recombinant Bispecific Monoclonal Antibodies Prepared by the Dock-and-Lock Strategy for Pretargeted Radioimmunotherapy - Sharkey, Robert M. (2010)
The selective delivery of therapeutic radionuclides is a promising approach for treating cancer. Antibody-targeted radionuclides are of particular interest, with two products approved for the treatment of certain forms of non-Hodgkin lymphoma. However, for many other cancers, radioimmunotherapy (RAIT) has been ineffective, being limited by prolonged exposure to the highly radiosensitive bone marrow. An alternative approach, known as pretargeting, separates radionuclide from the antibody, allowing the radiation to be delivered on a small molecule that can quickly and efficiently migrate into the tumor, and then rapidly clear from the body with minimal retention in tissues. Several pretargeting methods have been developed that differ in the way they selectively capture the radionuclide. This review focuses on the development of a novel form of bispecific monoclonal antibody (bsMAb) pretargeting that uses a unique radiolabeled hapten-peptide system that can be modified to bind a number of therapeutic and imaging radionuclides. Together with a specialized recombinant humanized bsMAb prepared with by a technique known as the Dock-and-Lock (DNL) method, this pretargeting procedure has been examined in a number of different animal models, showing a high level of sensitivity and specificity for localizing tumors, and improved efficacy with less hematologic toxicity associated with directly radiolabeled IgG. The bsMAb is a tri-Fab structure, having 2 binding arms for the tumor antigen and one capable of binding a hapten-peptide. Preclinical studies were preformed to support the clinical use of a bsMAb (TF2) and a hapten-peptide bearing a single DOTA moiety (IMP-288). A Phase 0 trial found an (131)I-TF2 that targets carcinoembryonic antigen (CEA) was stable in vivo, quickly clears from the blood, and localizes known tumors. The first-in-patient pretargeting experience with the (111)In-IMP-288 also observed rapid clearance and low tissue (kidney) retention, as well as localization of tumors, providing initial promising evidence for developing these materials for radioimmunotherapy.